Relationship Between Instagram Usage and Stress Among College Students - Rajani Aithal (CV. Doki Course and Training, 2026)
The present study examined the relationship between Instagram usage and stress among college students. Social networking applications have become deeply embedded in students' academic, social, and emotional lives, and concerns have increased regarding the mental health effects of excessive use. The study aimed to determine whether higher levels of Instagram usage are associated with greater stress among college students. A sample of 150 degree college students from Mysuru city, Karnataka, was selected randomly for the study. The sample included 75 male students and 75 female students, and the age of the participants ranged from 18 to 25 years, with a mean age of 23.16 years and a standard deviation of 1.91 years . Data were collected using the Test for Instagram Addiction (TIA; D'Souza et al., 2018) and the stress component of the Depression Anxiety Stress Scales-21 (DASS-21; Lovibond & Lovibond, 1995). Pearson's product-moment correlation and regression analysis were used to analyze the data. The results showed that all dimensions of Instagram addiction were positively and significantly related to stress, and the total Instagram addiction score was also positively correlated with stress, indicating that higher Instagram addiction is associated with higher stress among college students. The findings suggest that excessive and obsessive Instagram use may contribute to psychological strain in students, and the study highlights the need for awareness, prevention, and healthy digital behavior among young adults.